The Cellulolytic Activity And Volatile Fatty Acid Product Of Rumen Bacteria Of Buffalo And Cattle On Rice Straw, Elephant Grass, and Sesbania Leaves Substrates - Prayitno, Caribu Hadi; Hidayat, Nur (ANIMAL PRODUCTION, 1999)
Experiment on The Cellulolytic Activity and Volatile Fatty Acid Product of Rumen Bacteria of Buffalo and Cattle on Rice Straw, Elephant Grass, and Sesbania Leaves Substrates had been conducted at Feedstuff Laboratory of Animal Science Soedirman University. The basic design  that was used in this experiment was Completely Randomized Design (CRD) with factorial pattern of 6 x 3, three replications. The bacteria isolate as the factors were cellulolytic rumen bacteria isolate of buffalo (A1, A2, and A3) and cattle (A4, A5 and A6) while the substrates (second factor)  were NDF rice straw (S1), elephant grass (S2), and sesbania leaves (S3) Cell walls. The result of this experiment showed that the interaction between bacteria isolate and substrate  type were significant on pH, NDF digestibility, cellulase activity, pH was  6.28 until 6.43.  The NDF digestibility range was 12.27 until 55.61 percent. The lowers of cellulase activity was 5.11 IU/ml and the higher was 24.47 IU/ml. The range of acetic acid yield was 63.37 to 307.467 mg/100 ml. Range of  propionic production was 15.17 to 352.20 mg/ 100 ml. The production of butiric acid was 8.77 to 40.87 mg/ 100 ml. The cellulase activity  of cellulolytic rumen bacteria of buffalo was higher than cattle, and also their effect on NDF digestibility of rice straw, elephant grass, and sesbania leaves cell walls. The A3 of cellulolytic rumen bacteria isolate of  buffalo changed cell walls substrat to volatile fatty  acid was more effective than cattle, especially on cell elephant grass. Propionic and butiric  acid that was produced by cellulolytic rumen bacteria isolate of buffalo more higher than cattle (Animal Production 1 (1) : 1-9 (1999)Key Words: Cellulolytic, VFA, Rumen Bacteria, Buffalo, Cattle.